1798 Ky. Acts 106, ch. 54, § 5 - (:unkn) unknown (General Publisher, 1798)
Prohibited “negro, mulatto, or Indian” from possessing or carrying a gun, powder, shot, club, or other weapon or ammunition.
--
Keywords: ENSLAVED PERSONS & OTHER MINORITIES